ANALYSIS OF OSINT TOOLS FOR RESEARCHING SOCIAL NETWORKS - MOGYLEVYCH, DMYTRO; MOHYLEVYCH, VADYM; KONONOVA, IRYNA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article discusses the importance of social networks as a source of intelligence and analyzes the features of using specialized tools to obtain, process, and analyze data from various social platforms. The effectiveness of using social media for OSINT depends on the research goals, the type of information sought, the target audience, and the technical capabilities of the platform. The combined use of multiple sources allows you to create a holistic picture of the research object and increase the accuracy of analytical conclusions. Given the rapid growth of open data on Facebook, Twitter (X), and Instagram, modern OSINT tools have been classified and evaluated according to their functional purpose, collection methods, analytical capabilities, and information visualization. The advantages and limitations of both official APIs (Graph API, Twitter API, Instagram Graph API) and unofficial solutions (Twint, OSINTgram, Maltego with extensions, archiving tools, etc.) are analyzed. It was found that the effective use of OSINT tools depends on the technical characteristics of the platform, data availability, privacy policy, and the stability of the tools in the context of constantly changing interfaces and restrictions. The importance of visual analysis and geolocation, the role of cross-platform integration and archiving as elements of digital forensics are emphasized. The capabilities and limitations of OSINT tools designed for social network research are identified. It concludes that technical solutions must be combined with legal and ethical approaches to ensure the reliability, security, and legitimacy of OSINT research. The study emphasizes the importance of choosing the right approach to data collection and analysis depending on the functional characteristics of each social network in order to achieve maximum efficiency and relevance of the information obtained.
Keywords: OSINT; open sources of information; social networks; digital security; information threats